The intervention of Islamic Religious Education Teachers in Puberty Assistance: NVIVO Analysis - Faqihuddin, Achmad; Muflih, Abdillah; Syarifudin, Iif; Romadhon, Fajar; Sholachuddin Al-Ayyubi (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research explores the role of Islamic Religious Education (PAI) teachers in accompanying students during puberty, a critical transition phase in the lives of Muslim adolescents that involves significant physical, emotional, and spiritual changes. Appropriate assistance during this period is crucial to help teenagers understand the changes occurring and carry out their religious responsibilities well. Using a qualitative approach with phenomenological methods, this research involved in-depth interviews with 10 PAI teachers from elementary and junior high schools. The analysis using NVivo 12 shows that the PAI teacher's role includes religious education, emotional guidance, spiritual formation, and social facilitation. Despite facing unique challenges, PAI teachers overcame them with various adaptive and responsive strategies. Through intensive personal guidance, key strategies that have proven effective include creating a supportive and open environment where students feel comfortable discussing sensitive topics. This research highlights the importance of a holistic and integrative approach in assisting puberty and provides practical recommendations such as [specific recommendations] to increase the effectiveness of this assistance. This research contributes to the Islamic religious education literature by providing new insights into the multifaceted role of PAI teachers and the challenges they face, as well as suggesting strategies for improving student support during puberty.